Analisis Kesalahan Materi Dimensi Tiga Pada Siswa Kelas Xi Smk Miftahul Ulum Muncar - Whyma Fathul Muslich (Program Studi Tadris Matematika Universitas KH. Mukhtar Syafaat Banyuwangi, 2025)
The purpose of this research was to know: (1) errors made grade XI SMK Miftahul Ulum Muncar in solving three-dimensional problems; and (2) the factors that caused the error XI SMK Miftahul Ulum Muncar in solving three-dimensional problems. Subjects in this research were 27 students class XI TKJ 2, and the subjects were interviewed in this study consisted of 4 people with the criteria: (1) students who made a lot of mistakes in answering each item; and (2) variation of the mistakes made by the students, form of concepts error, principles, procedural, and technical. The results in this research were: (1) the type of errors made by students in completing a three-dimensional problem includes concepts errors, principles, procedural, and technical; and (2) factors causing errors by students in solving three dimensions, namely: a lack of prerequisite knowledge of students, low student motivation, lack of understanding concepts, students can’t prepare systematic steps to resolve the matter, and the carelessness of students.